Adaptation of Academic Self-Efficacy Measuring Tools using the Confirmatory Factor Analysis (CFA) - Esty Aryani Safithry (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Students with higher self-efficacy, are more self-confident, can set higher learning goals, and are better at problem solving, which may lead to better academic performance. This research aims to adapt and validate The Scale of Sources of Self-efficacy in Mathematics (SSSEM) in the context of Indonesian culture and language and test its reliability in high school students. The research sample consisted of 200 students from six high schools in the city of Palangkaraya. All items were analyzed using Confirmatory Factor Analysis (CFA). The research results show the construct validity of the instrument with the index criterion value ?2 = 170.749 p = 0.97 or (p-value > 0.05) meaning there is a match between the data and the model, then the RMSEA value = .028 (≤ 0.09), CMIN/DF = 1.154 (≤ 2.00), GFI = 0.920, CFI = 0.994, TLI = 0.993 and AGFI = 0897 (≥ 0.90). The results of the reliability analysis show that the scale has an adequate level of reliability. Then the construct reliability has good reliability with coefficient values for each dimension of 0.89 0.88, 0.89 and 0.87. Cronbach's Alpha value is above 0.70. This adapted scale had a good fit with empirical data after several modifications. Therefore, the Indonesian version of the SSSEM can be used as a valid and reliable measuring tool to measure self-efficacy in high school students in Indonesia.